Comparison of triglyceride-glucose index and triglyceride-glucose related indexes in predicting cardiovascular disease incidence among populations with cardiovascular-kidney-metabolic syndrome stages 0-3: a nationwide prospective cohort study - Qingsong Mao; Nianzhou Liu; Tian Xiong; Xinyi Wang; Xinling Tian; Yuzhe Kong (Frontiers in Endocrinology)
BackgroundThe association of the triglyceride glucose (TyG) index and related TyG metrics with obesity indices has been demonstrated to correlate with the incidence of cardiovascular disease (CVD). Nonetheless, this relationship has not been thoroughly investigated in patients with cardiovascular-kidney-metabolic (CKM) syndrome stages 0-3.MethodsThis study involved 7364 participants from the China Health and Retirement Longitudinal Study (CHARLS). Cox risk regression and restricted cubic spline (RCS) regression were used to analyze the correlation between the TyG index and related TyG indicators and the incidence rate of cardiovascular disease. To compare predictive performance, time-dependent Harrell’s C-indices, net reclassification index and integrated discrimination improvement were conducted.ResultsResearch shows that the TyG index and all TyG-related indexes can predict the incidence rate of CVD. RCS regression analysis showed that all indicators were linearly related to the incidence rate of CVD. The linear relationship between TyG and waist circumference (TyG-WC) or waist-to-height ratio (TyG-WHtR) still exists in CKM stages 1, 2, and 3. Compared with the TyG index (C-index: 0.611, p<0.001) and TyG-BMI (C-coefficient: 0.616, p<0.001), TyG-WC (C-index: 0.621, p<0.001) and TyG-WHtR (C-index: 0.621, p<0.001) have better effects on predicting the incidence rate of CVD.ConclusionBoth the TyG index and the TyG-related index are independent predictors of the incidence rate of CVD in patients with CKM syndrome stage 0-3. Importantly, TyG-WC and TyG-WHtR have a better predictive effect.